Effects of Feed Supplemented with Fermented Pine Needles (Pinus ponderosa) on Carcass Quality, Meat Quality, and Antioxidant Capacity of Growing–Finishing Pigs - Wenfeng Ma; Zhuo Ma; Pei Mao; Xiaoli Zhang; Xiaohong Wu; Mengmeng Gao; Qiujue Wu (Foods)
The purpose of this study was to investigate the effects of fermented pine needles on the carcass traits, meat quality, and antioxidant capacity of finishing pigs. In total, 80 Duroc × (Landrace × Large white) crossbred pigs of approximately 4 months of age, with an initial body weight of 60.5 ± 2.5 kg, were randomly assigned to four experimental treatments, which were then denoted as the control treatment (basal diet), the fermented pine needle (FR) 1 treatment, the FR2 treatment, and the FR3 treatment (the pigs were fed the basal diet supplemented with 1.0, 2.0, and 3.0% fermented pine needles, respectively) for 55 d. The obtained results showed that, compared with the CON group, the fermented pine needle treatments increased the lean meat percentage, total antioxidative capacity, and superoxide dismutase activity in the serum and longissimus dorsi muscle. In addition, the treatments increased the mRNA expression levels of SOD1, catalase, and Nrf2 in the muscle and decreased the malondialdehyde activity in the serum and longissimus dorsi muscle and the Keap1 mRNA expression level. Compared with the CON and FR1 treatment, the FR2 and FR3 treatments increased springiness, serum GSH-Px activity, and longissimus dorsi muscle CAT activity, and decreased hardness, chewiness, gumminess, and cohesiveness. Moreover, compared with the CON treatment and other fermented pine needle treatments, the FR2 treatment not only significantly elevated the carcass weight, dressing percentage, pH24h, a* value (redness), and marbling scores of the finishing pigs, but also remarkably reduced the L* value (lightness), b* value (yellowness), and shear force in the meat quality. In conclusion, the experiment indicated that the addition of fermented pine needles to the diet has no negative impact on the carcass characteristics of finishing pigs and could improve the tenderness and freshness of the meat, as evidenced by the modified antioxidant enzyme activity and mRNA expression levels of antioxidant genes in the muscles of finishing pigs.